(untitled) (Indian Journal of Public Health Research & Development, 2023)
Abstract Background: Spinal anaesthesia is the most preferred regional anaesthesia technique as it is easy to perform, economical and produces rapid onset of anaesthesia and complete muscle relaxation. The aim of intrathecal local anaesthetic is to provide adequate sensory and motor block necessary for all infra umbilical surgeries. Aims and Objectives: The aim of the study is to compare the Onset and Duration of Sensory Block; Onset and Duration of Motor Block and other factors in two groups i.e., Hyperbaric Bupivacaine 0.5% with Clonidine 30μg &Hyperbaric Bupivacaine 0.5% with Magnesium sulphate 50 mg when given intrathecally. Materials and Methods: A Comparative three group randomized clinical study with 90 patients with 30 patients in Group C (Clonidine), 30 patients in Group M (Magnesium) and 30 patients in Group N (Normal saline) to study the onset of motor and sensory block, changes in hemodynamics and side effects. Results: Our study has demonstrated that Intrathecal clonidine (30 mcg) prolonged post-operative analgesia along with earlier onset and prolonged duration of sensory and motor blockade compared to both magnesium (50 mg) and control.Intrathecal magnesium (50 mg) also increased the analgesic duration compared to control but it was associated with delayed onset of both sensory and motor blockade compared to both clonidine and control. Conclusion: Clonidine can be a good alternative adjuvant with 0.5% hyperbaric bupivacaine when compared to others like fentanyl, magnesium, midazolam, ketamine etc. as it provides early onset of sensory and motor blockade and also prolonged duration of post-operative analgesia.